Xenoduplex Analysis—A Method for Comparative Gene Mapping Using Hybrid Panels - Marklund, Lena; Jeon, Jin-Tae; Andersson, Leif

(untitled) (Genome Research, 1998)
Somatic cell hybrid (SCH) panels and radiation hybrid (RH) panels are powerful resources for comparative gene mapping because gene assignments are made without the detection of genetic polymorphism as needed for linkage mapping. A frequently encountered problem, however, is that the gene specific primers may amplify homologous PCR products of equal length from the donor and recipient species of the panel. Here, we describe a simple solution to this problem in which we utilize the formation of interspecies heteroduplexes that can be easily distinguished from the corresponding homoduplexes by native polyacrylamide gel electrophoresis. We denote these DNA–DNA interspecies hybrids, xenoduplexes (xeno = Gr. Xenos, foreigner). A merit of the method is that the formation of xenoduplexes strongly suggests that the PCR products from the two species represent homologous sequences. The method is thus particularly useful for comparative gene mapping when the PCR primers have been designed by use of sequence information from other species. In this study we have successfully used xenoduplex analysis and a pig-rodent SCH panel to map seven porcine genes (ACADM, AT3, HOXD, IL8RB, LEPR, PAX8, PKLR) for which no previous sequence information was available. The assignment of the leptin receptor gene (LEPR) to pig chromosome 6q32–35 excluded LEPR as a candidate gene for a QTL on pig chromosome 4 with a major effect on fatness.